Selective Inhibition of Orexin-2 Receptors Prevents Stress-Induced ACTH Release in Mice - Yun, Sujin; Wennerholm, Michelle; Shelton, Jonathan E.; Bonaventure, Pascal; Letavic, Michael A.; Shireman, Brock T.; Lovenberg, Timothy W.; Dugovic, Christine (Frontiers in Behavioral Neuroscience, 2017)
Orexins peptides exert a prominent role in arousal-related processes including stress responding, by activating orexin-1 (OX1R) and orexin-2 (OX2R) receptors located widely throughout the brain. Stress or orexin administration stimulates hyperarousal, adrenocorticotropic hormone (ACTH) and corticosterone release, and selective OX1R blockade can attenuate several stress-induced behavioral and cardiovascular responses but not the hypothalamic-pituitary-adrenal (HPA) axis activation. As opposed to OX1R, OX2R are preferentially expressed in the paraventricular hypothalamic nucleus which is involved in the HPA axis regulation. In the present study, we investigated the effects of a psychological stress elicited by cage exchange on ACTH release in two murine models (genetic and pharmacological) of selective OX2R inhibition. Cage exchange-induced stress produced a significant increase in ACTH serum levels. Mice lacking the OX2R exhibited a blunted stress response. Stress-induced ACTH release was absent in mice pre-treated with the selective OX2R antagonist JNJ-42847922 (30 mg/kg po), whereas pre-treatment with the dual OX1/2R antagonist SB-649868 (30 mg/kg po) only partially attenuated the increase of ACTH. To assess whether the intrinsic and distinct sleep-promoting properties of each antagonist could account for the differential stress response, a separate group of mice implanted with electrodes for standard sleep recording were orally dosed with JNJ-42847922 or SB-649868 during the light phase. While both compounds reduced the latency to non-rapid eye movement (NREM) sleep without affecting its duration, a prevalent REM-sleep promoting effect was observed only in mice treated with the dual OX1/2R antagonist. These data indicate that in a psychological stress model, genetic or pharmacological inhibition of OX2R markedly attenuated stress-induced ACTH secretion, as a separately mediated effect from the NREM sleep induction of OX2R antagonism.